Message from Irina Bokova, Director-General of UNESCO on the occasion of the 2nd International Conference: Linguistic and Cultural Diversity in Cyberspace, Yakutsk, Russian Federation, 12-14 July 2011 - UNESCO. Director-General, 2009-2017 (Bokova, I.G.) (12 July 2011, 2011)
Electronic version only